Inpatient Dermatology: A 59-Year-Old Female With Painful Bullae and Erythema of the Lower Extremities - Laura Hinkle; Alvaro Lapitz (Association of American Medical Colleges, 2010)
Abstract This PowerPoint presentation serves as an interactive self-study module designed for use by medical students in both preclinical and clinical years. The resource is presented as an interactive case study of a patient with bullous lesions, followed by a review of how to evaluate the patient, how to develop a differential diagnosis, and how to provide basic treatment. This tutorial features both clinical and dermatopathology images and a diagram to help learners better understand the information presented. Medical students at our institution have reviewed this resource, and they have given us positive feedback regarding the success of this resource in meeting the stated objectives.